Seroprevalence of trichinellosis in pigs slaughtered in Bodija abbattoir Oyo State Nigeria (2012)
This survey was carried out to determine the prevalence of trichinellosis in Bodija municipal abattoir of Oyo state, Nigeria. Sera samples were collected from pigs slaughtered on the slabs from July to November, 2010 and taken to the laboratory in the department of Veterinary Microbiology and Parasitology, University of Ibadan for analysis. The samples were processed for Trichinella antibodies by ELISA using excretory-secretory (E/S) antigen.246 samples were collected and a prevalence of 15.04% was recorded. Adult pigs had a higher prevalence (35.55%) than the young (8.40, 14.29) and prevalence in male pigs was slightly higher (19.80%) than the females (11.72%) though this prevalence is not statistically significant